Comparative study of high hydrostatic pressure and high temperature short time processing on quality of clear and cloudy Se-enriched kiwifruit juices. (October 2018) - Xu, Xinxing; Deng, Jingjing; Luo, Dongsheng; Bao, Yejun; Liao, Xiaojun; Gao, Haiyan; Wu, Jihong
Abstract: Selenium (Se) distribution was investigated and a comparative study was carried out into the effects of high hydrostatic pressure (HHP) and high temperature short time (HTST) treatments on quality for both clear and cloudy Se-enriched kiwifruit juice (clear-SKJ, cloudy-SKJ). Organic Se which accounted for 62.32% has a wider distribution than inorganic Se in kiwifruits and mainly comprising Se-protein and Se-polysaccharide. The process of separating kiwifruit pomace from juice caused significant decline in Se content with 43.07% and 49.04% in cloudy and clear juices respectively, and the sterilization process of HHP and HTST significantly decreased the Se contents from 50.46 ± 0.42 μg/kg to 39.63 ± 0.51 μg/kg and 37.93 ± 0.08 μg/kg in cloudy-SKJ, respectively. During the storage period, HTST- and HHP-processed juices showed no significant differences in total Se content, and similarly for certain chemical-physical qualities of total soluble solids, titratable acid, viscosity and pH. In addition, HHP (500 MPa/10 min) and HTST (110 °C/8.6 s) treatments inactivated yeasts and molds (Y&M) completely and sustained total aerobic bacteria (TAB) counts below 2.0 Log10 CFU/mL which guaranteed the microbiological safety in clear-SKJ during storage at 4 °C and 25 °C for 42 days, but TAB counts were detected >2.0 Log10 CFU/mL which demonstrated a shorter shelf life in cloudy-SKJ under the same storage conditions. Moreover, the HHP-treated sample showed better quality characteristics compared with the HTST-treated sample during 42-day storage except for total phenols and the storage time at 4 °C was more conducive to the preservation of the juices after HHP and HTST treatments. Industrial relevance: Se-enriched kiwifruit juice is a promising Se-enriched beverage product which has high nutrition and economic value. The results obtained underline the different effects of HHP and HTST on quality and storage stability of Se retention, microorganisms, color, total phenols, chlorophyll a nd other quality-related aspects. This study may provide technical support for the application of HHP or HTST in the Se-enriched kiwifruit juice industry. Furthermore, a non-thermal technique which can improve functional juice properties to meet the demand of consumers for healthier products is provided in this study. Highlights: Se distribution in Se-enriched kiwifruits was evaluated. Processing loss of Se, ascorbic acid, total phenols, chlorophyll were detected. Effects of HHP and HTST on quality of clear- and cloudy-SKJ were compared. Original color, ascorbic acid and chlorophyll were kept better immediately after HHP. Safer products were obtained during storage at 4 °C than 25 °C.